The Mediating Role of Work-Life Balance in the Relationship between Workload, Compensation, And Job Satisfaction - Saputra, Aditya; Nawangsari, Lenny Christina (Journal of Sustainable Economic and Business, 2025)
Objective: This study aims to describe how Work-Life Balance Mediate the Relationship between Workload, Compensation, and Job Satisfaction.Methodology: This study uses a quantitative approach with survey method, data research were taken from 120 employees at PT PLN (Persero) UPT Pulogadung and analyzed using SmartPLS 3.2.9 version.Findings: The data analysis showed that workload has a negative and significant effect on job satisfaction, compensation has a positive and significant effect on job satisfaction, workload has a negative and significant effect on work-life balance, compensation has a positive and significant effect on work-life balance, work-life balance has a positive and significant effect on job satisfaction, work-life balance partially mediates the negative relationship between workload and job satisfaction, work-life balance partially mediates the positive relationship between compensation and job satisfaction.Conclusion: Worklife Balance plays a role in mediating the negative and significant relationship between current workload and job satisfaction, and Worklife Balance plays a role in mediating the positive and significant relationship between compensation and job satisfaction.